Exploration of changes in health-related behaviours among Saudi Arabian undergraduates in the UK. (5th May 2021) - Alzain, Hassan Mohammed; Leavey, Conan; Mitchell, Graeme; Gee, Ivan; Hall, Jason; Al-Subaie, Abdullah Saad
Summary: This project is an exploratory survey of the ways in which living in the UK has affected the health-related behaviours of Saudi Arabian undergraduate students. The study identifies changes in exercise behaviours, dietary and smoking habits and experiences of stress after their move to the UK. In addition, it identifies what the students perceive to be the drivers of these changes. To achieve this, an online questionnaire was developed collecting quantitative data. This was distributed via Facebook groups specifically for Saudi students in the UK. The results demonstrate that a majority of Saudi Arabian undergraduates felt that their behaviours had become healthier since their move to the UK, mainly as a result of a more active lifestyle, derived from reduced reliance on cars, increased daily walking, and a heightened focus on health promoted by their independence, the availability of healthy foods and exposure to a more health-promoting culture. Although these results are based on a relatively small sample, they are surprising since they contradict previous studies on international students, which have generally found negative lifestyle changes during their studies, including increased stress, poorer dietary habits and a decline in physical activity. Although the exploratory nature of the study means that concrete recommendations cannot be made, it nonetheless offers an impetus for further research into how Saudi Arabian students may be encouraged to adopt healthier lifestyles while studying in the UK.